Integration Ukrainian economy into European value chains: modeling of economic complexity - Пирог, О. В.; Pyroh, O. V. (Видавництво Львівської політехніки, 2024)
Досліджено сучасні тенденції інтеграції України в європейські ланцюги доданої вартості та виявлено її особливості протягом останніх років (2000-2021 рр.). На основі останніх досліджень та публікацій щодо глобальних ланцюгів доданої вартості (ГЛДВ) можна сформулювати гіпотезу про те, що в післявоєнний період Україні доцільно інтегруватися в європейські ланцюги доданої вартості шляхом трансформації галузевої моделі розвитку, яка забезпечить статус глобального та конкурентоспроможного актора у світовій та європейській економіках. Протягом 2000-2021 років в ГЛДВ Україна торгувала продукцією в таких видах економічної діяльності, як сільське, лісове господарство та рибальство; електроенергія, газ і вода; добувна промисловість і розроблення кар’єрів; переробна промисловість та послуги. Встановлено, що відбулись суттєві зміни в географічній структурі торгівлі України в ГЛДВ, а також змінився напрям зовнішньоекономічної діяльності України: з “вектора Росія-СНД” до “вектора ЄС”. Отримані результати можуть бути використані під час розробки рекомендацій щодо формування та реалізації стратегії інтеграції України в європейські ланцюги доданої вартості в умовах війни та післявоєнний період.

Purpose. The purpose of the paper is to research of the modern trends of Ukrainian integration into European value chains that based on the sectoral model and its complexity, and to identify their features during last years. Based on the latest research and publications related to this topic, it is possible to formulate the hypothesis that at the postwar period, Ukraine needs to integrate into European value chains via transformation of the sectoral model of development that will provide the status as global and competitive actor in global and European economies. Design/methodology/approach. To research the modern trends of Ukrainian integration into European value chains, the methods of scientific research were applied (theoretical generalization, empirical method and methods of statistical analysis). Findings. Our research observed the modern tendencies of Ukrainian economy integration into European value chains. During 2000-2021 Ukraine traded the products in such types of economic activities as agriculture, forestry and fishing; electricity, gas and water; mining and quarrying; manufacturing, and services in GVCs. There were also significant changes in the geographical structure of Ukraine’s trade in GVCs, and, also, changed the direction of Ukraine’s foreign economic activity: from the “Russia-CIS vector” to the “EU vector”. Practical implications. The obtained results impact to develop the recommendations for the formation and implementation of the strategy of Ukrainian integration into European value chains now and at the conditions of postwar period. Originality/value. The research highlights the elements of the methodological system of transformation of the integration strategy of Ukraine into European value chains now and at the conditions of the postwar period, based on macro-forecasting of the country’s development was carried out in accordance with strategic economic tasks.
Інтеграція української економіки в європейські ланцюги доданої вартості: моделювання економічної складності
Keywords: європейські ланцюги доданої вартості; економічна складність; структура економіки; Україна; ЄС; global value chains (GVCs); European value chains (EUVCs); economic complexity; structure of economy; Ukraine; EU; F15; 330.341; 339.94